2009
DOI: 10.2478/v10053-008-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Designing informative warning signals: Effects of indicator type, modality, and task demand on recognition speed and accuracy

Abstract: An experiment investigated the assumption that natural indicators which exploit existing learned associations between a signal and an event make more effective warnings than previously unlearned symbolic indicators. Signal modality (visual, auditory) and task demand (low, high) were also manipulated. Warning effectiveness was indexed by accuracy and reaction time (RT) recorded during training and dual task test phases. Thirty-six participants were trained to recognize 4 natural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…It is used to formulate theories of brain function and cognitive processing (Ratcliff & Smith, 2004), to evaluate training regimens, user interface design, vehicle operation and task design (e.g., Borowsky, Oron-Gilad, & Parmet, 2009;Stevens, Brennan, Petocz, & Howell, 2009;Sullivan, Tsimhoni, & Bogard, 2008), and to evaluate medical conditions, especially schizophrenia, learning disorders, and other psychological disorders (e.g., Heiervang & Hugdahl, 2003;Querne & Berquin, 2009;Shakow, 1977). RT has been used as a window on psychological processes for almost two centuries and it forms the foundation for most work in cognitive psychology.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to formulate theories of brain function and cognitive processing (Ratcliff & Smith, 2004), to evaluate training regimens, user interface design, vehicle operation and task design (e.g., Borowsky, Oron-Gilad, & Parmet, 2009;Stevens, Brennan, Petocz, & Howell, 2009;Sullivan, Tsimhoni, & Bogard, 2008), and to evaluate medical conditions, especially schizophrenia, learning disorders, and other psychological disorders (e.g., Heiervang & Hugdahl, 2003;Querne & Berquin, 2009;Shakow, 1977). RT has been used as a window on psychological processes for almost two centuries and it forms the foundation for most work in cognitive psychology.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of informationization as well as the development of human–computer interactions, icons have become an important component of digital user interfaces ( Li, Chen, Sha, & Lu, 2017 ; Nakamura & Zeng-Treitler, 2012 ). Compared with words, graphic symbols are able to transcend language barriers ( Bocker, 1996 ; Caplin, 2001 ; Stevens, Brennan, Petocz, & Howell, 2009 ) and convey large amounts of information in a more concise and efficient way ( Amer & Maris, 2007 ; Chi & Dewi, 2014 ; Ells & Dewar, 1979 ; Huang, Bias, & Schnyer, 2015 ; Muter & Mayson, 2007; Perry, Stevens, Wiggins, & Howell, 2008 ). However, people are still likely to misinterpret the meanings of icons that are poorly designed.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because research has consistently demonstrated that auditory signals with a close relationship between the sound and referent (meaning) are learned more easily, especially if they use soundbased metaphors with the real world (Atyeo & Sanderson, 2015;Edworthy et al, 2013;Isherwood & McKeown, 2016). Sound-based metaphors are typically caricatures of environ-mental sounds such as coughing to indicate 'leaking gas' or the sound of a heartbeat to indicate that 'cardiovascular function needs to be checked' (Stevens et al, 2009;Edworthy et al, 2014). Medical alarm sounds, in contrast, tend to be either tonal sequences or beeps, buzzers and pings.…”
Section: Accessing Meaning From Alarmsmentioning
confidence: 99%